Dowmetal Magnesium: The Metal of Motion - Dow Chemical Company (1944)
Print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement features an illustrated depiction of man pushing a lawn mower alongside a hand lifting a winged ingot of magnesium. The accompanying text details Dow's extraction of magnesium from seawater and brine and Dowmetal's lightness and durability relative to other structural metals, as well as its use in war materials. This advertisement appeared on page 7 of the July 3, 1944 edition of Time.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Magnesium; Magnesium alloys; Magnesium industry and trade; Advertising; Advertising, Industrial; World War (1939-1945)